Paramedics’ perception on video assisted learning method in learning emergency skills - Bala Krishnian R. Muniandy; Ahmad Khaldun Ismail; Hamidah Yusoff; Mohd Johar Jaafar; Ismail Mohd Saiboon (Fakulti Perubatan, UKM, 2016)
Information technology use in healthcare education has become a popular medium of instruction. One of the medium of instruction is video assisted learning (VAL). The use of VAL as an instructioemergency skills is not new. However, there are lack of studies on the perception of using this method in learning emergency skills. This qualitative study involved four focused discussion groups following a VAL instruction on emergency skills. A total of 20 paramedics were divided into four groups. They were involved in a focussed discussion after a VAL instruction session. Findings reveal that the paramedics perceived three major themes which were categorized as : i) advantages of video as teaching tool, ii) barrier in using video as a teaching tool; and iii) suggestions on using video as teaching tool. The findings indicate that the paramedics perceived VAL as a potential tool for learning emergency skills. However, they suggested the language of instruction should be in their mother tongue for better understanding. This implies that using English language has disadvantage in technology enhanced learning for better understanding.